Toxoplasmosis Presenting as Nonhealing Cutaneous Ulcer - M. Adhikari; S. Dhakal; S. Bhattarai; U. Rai (Hindawi Limited, 2020)
Introduction. Systemic manifestation of toxoplasmosis is commonly seen in immune-compromised individuals. Skin manifestations are seen commonly in conjunction with systemic features. Isolated cutaneous toxoplasmosis is extraordinarily rare in immunocompetent patients. Case Description. A 64-year-old female presented to the Dermatology Outpatient Department (OPD), with a nonhealing ulcer over dorsum of the left hand for one year. The patient did not have any systemic diseases. Serology tests were negative. An incisional biopsy of the lesion revealed dense inflammatory cell infiltrates comprising predominantly of plasma cells and lymphocytes, multinucleated giant cells, and focal abscess formation in the dermis. Periodic Acid Schiff (PAS) stain showed organisms in the dermis with morphological resemblance to tachyzoites of Toxoplasma gondii. Conclusion. Though rare, a possibility of primary cutaneous toxoplasmosis should always be considered and looked for, even in immunocompetent patients presenting with chronic nonhealing ulcers.